2012
DOI: 10.1097/pas.0b013e31824b1ee0
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Pulmonary Angiomatoid Fibrous Histiocytoma

Abstract: Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue neoplasm of intermediate biological potential, predominantly occurring in the extremities of children and young adults. It has only recently been reported as a primary lung tumor. We describe 2 cases arising endobronchially harboring EWSR1 gene rearrangements by fluorescence in situ hybridization and, respectively, EWSR1-CREB1 and EWSR1-ATF1 gene fusions by reverse transcription polymerase chain reaction. Histologically, both tumors showed classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 29 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…10 Despite desmin negativity and lack of lymphoplasmacytic cuff, PPMS show some histologic overlap and similar genetic features with AFH, raising the possibility of a pulmonary myxoid variant of AFH. 11,12 A somewhat similar scenario is the GI clear cell sarcoma, a term initially proposed by us in keeping with a variant of soft tissue CCS lacking melanocytic differentiation, 3 but refuted by others, who suggested instead a novel entity designated as malignant gastrointestinal neuroectodermal tumor (GNET), possibly originating from a GI neuroectodermal precursor cell which has lost or does not have the potential to differentiate along the melanocytic lineage. 13 Some of these controversies stem from the uncertainty on how translocation events drive phenotypic variations, and larger datasets are needed to clarify their status as independent pathologic entities.…”
Section: Discussionmentioning
confidence: 97%
“…10 Despite desmin negativity and lack of lymphoplasmacytic cuff, PPMS show some histologic overlap and similar genetic features with AFH, raising the possibility of a pulmonary myxoid variant of AFH. 11,12 A somewhat similar scenario is the GI clear cell sarcoma, a term initially proposed by us in keeping with a variant of soft tissue CCS lacking melanocytic differentiation, 3 but refuted by others, who suggested instead a novel entity designated as malignant gastrointestinal neuroectodermal tumor (GNET), possibly originating from a GI neuroectodermal precursor cell which has lost or does not have the potential to differentiate along the melanocytic lineage. 13 Some of these controversies stem from the uncertainty on how translocation events drive phenotypic variations, and larger datasets are needed to clarify their status as independent pathologic entities.…”
Section: Discussionmentioning
confidence: 97%
“…Although rare in the thoracic or abdominal cavity, angiomatoid fibrous histiocytomas have been reported at these sites, harboring EWSR1-ATF1 fusions (40). Additionally, rare cases with endobronchial or pulmonary presentation have been described (41, 42). However, angiomatoid fibrous histiocytomas typically stain for desmin, while being consistently negative for cytokeratin.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported clear cells, rhabdomyoblast-like cells, pulmonary edema like pattern and myxoid stroma in some AFH cases [5]. Bohman et al have reported perineurioma-like pattern, moderate pleomorphism, significant areas of sclerosis, eosinophils in the stroma [12,13] [12,16] while consistently negative for S100 protein, CD34, CD35, CD21 and Cytokeratin. Our case shows immunopositivity for desmin, EMA and CD68.…”
Section: Discussionmentioning
confidence: 99%
“…Our index case was seen in 40 years woman with a recurrent thigh mass measuring 6 cm in maximum dimension. Microscopically, it is characterized by varying proportions of spindled or histiocytoid cells, arranged in a nodular pattern, pseudovascular spaces and prominent lymphoplasmacytic rim [12,13].…”
Section: Discussionmentioning
confidence: 99%